THE IMPLICATIONS OF THE DOCTRINE SAD PARAMITA INFORMING THE STUDENT CHARACTER OF SMK TOURISM GANESHA UBUD - Ni Nyoman Perni (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2019)
The teachings of Sad Paramita are moral teachings or ethics as the way to nobility. The doctrine of Sad Paramita as the basis of the Hindu religion that has a religious attitude to increase the nobility, behavior, and personality of man. In addition, Sad Paramita can build a balanced harmony of life. When the doctrine of Sad Paramita are realized in daily life, harmony, peace, welfare, and success will be accomplished. Based on the fact that steadreality to God begins with the confidence of the self, by believing in the presence of God and his doctrine. People who are said to have a right steadiness attitude will always obey, diligent and confident in the activity of something related to God or the power that is beyond the limits of human power. In this case, the problem of Taqwa (devoutly) will never be separated from the scope of religion, because religion is a path or belief that a person embraced in disobedience to his lord. If religion has become an integral part of the person of every Hindu, then religion will be visible in all human behavior both individually and jointly. Thus through the application of the doctrine of Sad Paramita is expected to be able to instill good character and possess noble nobility. Thus, the realization of the teaching, indirectly, can produce superior students, able to compete in the world of work or industry, possess skills and have high competitiveness, creative and innovative, and always uphold honesty.